Spin injection in indium arsenide - Johnson, Mark; Koo, Hyun C.; Han, Suk H.; Chang, Joonyeon (Frontiers in Physics, 2015)
In a two dimensional electron system (2DES), coherent spin precession of a ballistic spin polarized current, controlled by the Rashba spin orbit interaction, is a remarkable phenomenon that’s been observed only recently. Datta and Das predicted this precession would manifest as an oscillation in the source-drain conductance of the channel in a spin-injected field effect transistor (Spin FET). The indium arsenide single quantum well materials system has proven to be ideal for experimental confirmation. The 2DES carriers have high mobility, low sheet resistance, and high spin orbit interaction. Techniques for electrical injection and detection of spin polarized carriers were developed over the last two decades. Adapting the proposed Spin FET to the Johnson-Silsbee nonlocal geometry was a key to the first experimental demonstration of gate voltage controlled coherent spin precession. More recently, a new technique measured the oscillation as a function of channel length. This article gives an overview of the experimental phenomenology of the spin injection technique. We then review details of the application of the technique to InAs single quantum well (SQW) devices. The effective magnetic field associated with Rashba spin-orbit coupling is described, and a heuristic model of coherent spin precession is presented. The two successful empirical demonstrations of the Datta Das conductance oscillation are then described and discussed.